2022
DOI: 10.3341/kjo.2021.0128
|View full text |Cite
|
Sign up to set email alerts
|

Nonarteritic Anterior Ischemic Optic Neuropathy Following COVID-19 Vaccination: A Case Report

Abstract: To compare the refractive outcomes after cataract surgery between patients with and without pseudoexfoliation, and to evaluate the risk factors of refractive error. Methods:Retrospective review of 210 eyes with pseudoexfoliation (study group) and 510 normal eyes (control) that underwent uneventful phacoemulsification with intraocular lens implantation. The study group included pseudoexfoliation syndrome (PXS) and pseudoexfoliation glaucoma (PXG) subgroups. The main outcome measure was refractive error, defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Optic neuropathy is suspected as one of adverse events of the COVID-19 vaccine, which includes ON associated with or without demyelinating CNS diseases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], NA-AION [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and NMOSD [ 8 , 9 ]. Lotan et al reviewed 14 case reports and 2 case series by electronic searches of the published literature regarding neuro-ophthalmological complications of COVID-19 vaccines and reported that optic neuritis was the most common, occurring in 61 of 76 cases (80.3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optic neuropathy is suspected as one of adverse events of the COVID-19 vaccine, which includes ON associated with or without demyelinating CNS diseases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], NA-AION [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and NMOSD [ 8 , 9 ]. Lotan et al reviewed 14 case reports and 2 case series by electronic searches of the published literature regarding neuro-ophthalmological complications of COVID-19 vaccines and reported that optic neuritis was the most common, occurring in 61 of 76 cases (80.3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We finally obtained reports of 14 patients (16 eyes) from 9 centers, 1 of which had already been published in the literature. 12 …”
Section: Methodsmentioning
confidence: 99%
“…In Korea, where two recombinant mRNA vaccines (BNT162b2, Pfizer-BioNTech and mRNA-1273, Moderna) and two adenovirus vector-based vaccines (ChAdOx1 nCoV-19, Oxford-AstraZeneca and Ad26.COV2 Janssen, Johnson & Johnson) have been mainly distributed, a few cases of ocular disease after COVID-19 vaccination have been reported. 11 12 13 14 However, with the widespread distribution of vaccines, the need for a nationwide survey of ocular disease after COVID-19 vaccination has been raised.…”
Section: Introductionmentioning
confidence: 99%
“…NAION was reported after the Pfizer-BioNTech mRNA-based and AstraZeneca nonreplicating viral vector vaccines 138,139 . NAION was rarely reported to be associated with vaccination in the past.…”
Section: Neuro-ophthalmic Adverse Events To Coronavirus Disease 2019 ...mentioning
confidence: 99%